2020
DOI: 10.1002/nop2.659
|View full text |Cite
|
Sign up to set email alerts
|

Reflective capacity in nurses in specialist education: Swedish translation and psychometric evaluation of the Reflective Capacity Scale of the Reflective Practice Questionnaire

Abstract: Aim This study aimed to test the validity and reliability of the Swedish version of the Reflective Capacity Scale of the Reflective Practice Questionnaire in a nursing context. Design Non‐experimental and cross‐sectional. Methods The instrument was translated from English to Swedish using a translation and back‐translation procedure. Data for the validity and reliability analysis were collected from Registered Nurses in specialist education (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This mean was 4.27 ± 0.68 in mental health professionals and 3.51 ± 1.02 in the general population [ 4 ]. Gustafsson et al (2021) conducted their study on nurses enrolled in advanced level specialized training at two universities in northern Sweden and showed that the mean score of reflective capacity was 4.19 [ 31 ]. The results of a study on students in Spain indicated that students’ reflective capacity was at an almost average level (3.88) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mean was 4.27 ± 0.68 in mental health professionals and 3.51 ± 1.02 in the general population [ 4 ]. Gustafsson et al (2021) conducted their study on nurses enrolled in advanced level specialized training at two universities in northern Sweden and showed that the mean score of reflective capacity was 4.19 [ 31 ]. The results of a study on students in Spain indicated that students’ reflective capacity was at an almost average level (3.88) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the study by Priddis and Rogers (2018) obtained the highest mean in the dimension of RO (4.69 ± 0.68) and the lowest mean in the dimension of RiA (4.31 ± 0.70); the mean SA score in their study was 4.46 ± 0.74 [ 25 ]. In the study by Gustafsson et al (2021), the lowest mean was related to RiA (3.879) [ 31 ]. RO having the lowest mean in the current study may be attributed to culture.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, TSS was adapted from the theory of adult learning in the school organization support scale [ 44 ]. PF was adapted from the reflective capacity scale [ 45 ]. TSI was adapted from the Reflective Practice Questionnaire [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have been conducted utilising the RPQ with medical students ( Bari et al, 2021 ; Horst et al, 2019 ; Khoshgoftar & Barkhordari-Sharifabad, 2023a , 2023b ; Lee et al, 2023 ; Rogers et al, 2019 ; Schwartz et al, 2020 ; Van Winkle et al, 2021 , 2022 ), surgeons/physicians ( Aitken et al, 2021 ; Whelehan, Conlon & Ridgway, 2021 ), nurses ( Aitken et al, 2021 ; Al-Osaimi, 2022 ; Gabrielsson et al, 2022 ; Gustafsson et al, 2020 ; Khalil & Hashish, 2022 ), psychologists ( Sadusky & Spinks, 2022 ), allied health professionals ( Aurora, Mawren & Fullam, 2023 ; Or & Golba, 2023 ; Parrott et al, 2023 ), pre-service teachers ( Day, Webster & Killen, 2022 ; Fuertes-Camacho, Dulsat-Ortiz & Alvarez-Canocas, 2021 ), qualified teachers ( Chen & Chen, 2022 ; Gross, 2020 ; Moeder-Chandler, 2020 ), and sport coaches ( Da Silva et al, 2022 ). In these studies the RPQ has been used for a range of purposes, such as assessment of the reliability of the RPQ scales ( e.g ., Gustafsson et al, 2020 ), comparison between different sub-groups of participants ( e.g ., Day, Webster & Killen, 2022 ), and comparison across different time points to explore student development ( e.g ., Van Winkle et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In response to this we published a follow up article in 2019 proposing a single reflective practice score by averaging across the four reflective practice sub-scales of the RPQ ( Rogers et al, 2019 ). We were not surprised to see most of the subsequent studies utilising the RPQ made use of this more simplified conceptualisation of the reflective practice measure ( Al-Osaimi, 2022 ; Bari et al, 2021 ; Da Silva et al, 2022 ; Day, Webster & Killen, 2022 ; Gabrielsson et al, 2022 ; Gross, 2020 ; Gustafsson et al, 2020 ; Horst et al, 2019 ; Khalil & Hashish, 2022 ; Or & Golba, 2023 ; Schwartz et al, 2020 ; Van Winkle et al, 2021 , 2022 ; Whelehan, Conlon & Ridgway, 2021 ).…”
Section: Introductionmentioning
confidence: 99%